Acid matrix applications: well stimulation and completion fluids using viscoelastic surfactants and modified additives
By combining viscoelastic surfactant (VES) with modified nanomaterials, especially nanocell loss, to form a new thickener system, the stability and cost-effectiveness of VES technology in high temperature and complex saline environments is solved, and the improvement of high stability and self-separation acidic properties is achieved.
Patent Information
- Application Number
- JP2025010905
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-10-07
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-30
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing VES technology has poor stability under high concentration and high temperature conditions, poor performance in complex brine environments, and high cost, making it difficult to effectively control the viscoelasticity and cost-effectiveness.
The combination of viscoelastic surfactant (VES) with modified nanomaterials, especially nanocell loss, is used to form a new thickener system, which improves the stability and performance of nanomaterials through surface modification and polymer modification.
High stability and self-separation acidic properties under high temperature and high salt conditions are achieved, reducing costs, while improving fluidity and permeability, and enhancing adaptability to high temperature and complex environments.
Smart Images

Figure 2025069238000012 
Figure 2025069238000013 
Figure 2025069238000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition for forming an oil well or a gas well, a method for producing the composition, and a method for forming an oil well or a gas well. [Background technology]
[0002] Viscoelastic surfactants (VES) as part of fracturing fluid and proppant transport fluid compositions during fracturing processes are a departure from the use of polymeric thickeners, i.e., gels based on polymers such as natural guar and synthetic polyacrylamide. The viscosity of VES fluids is created by the self-assembly of small surfactant molecules in solution, which form spherical, rod-shaped and bicontinuous structures of lyotropic liquid crystalline ordered micelles. The entanglement of these flexible and more highly ordered micelles imparts increased viscosity to the solution. Hydraulic fracturing (HF) has been used for a long time in the completion phase of drilling, and various stimulation fluids have been developed over the years that can withstand high pumping speeds, shear stresses and high temperatures, as well as pressures in the borehole. In the completion phase of drilling (exploration and production), retained permeability and leak-off (fluid loss) control are two of the most important requirements. Ultimately, the main objective is to achieve a highly conductive pathway that does not damage or reduce the productivity of the completed well.
[0003]
[0003] Cross-linked polymer gels are the most common thickening media in several oilfield fluid compositions that provide good leak-off control. However, they may have a disadvantage in terms of retention permeability and low fluid loss performance if all the polymers introduced do not break down. VES as HF fluids have been reported in several patents (Patents 1-10, endnotes). They are polymer-free compositions and the viscosity is achieved mainly by controlling the concentration towards a higher ordered micellar structure, so they are easily recovered and do not require gel breakers for control. Furthermore, they can minimize fracture height growth and increase effective fracture length in achieving effective productivity from well completion operations. For VES fluids, elasticity and micellar structure rather than fluid viscosity are the main property enhancing factors. The key advantage is that VES fluids can stimulate efficiently with lower viscosity and reduced friction pressure, thus reducing the energy for fluid pumping towards larger fracture length (horizontal) and allowing better fracture geometry control in deeper formations. Other possible uses of VES technology include filter cake removal, selective matrix diversion, permeability preservation, and coiled tubing cleaning. However, VES has several drawbacks, such as 1) poor stability at high concentrations and temperatures, 2) poor stability in complex brine conditions or highly salt-saturated environments, 3) lack of viscoelastic control when deployed with other chemical components and additives, and 4) cost. Typical preferred dosages for stimulating and finishing operations using thickening polymers such as guar, xanthan gum, and polyacrylamide are about 2-3% of the water. Preferred dosages for VES are about 3-10% of the water. In general, the cost of VES thickeners can be up to three times the cost of polymer thickeners. It is important to justify any price difference with benefits such as thermal stability, brine stability, pressure control, pumping rate control, no degraders, easy cleaning, stimuli-responsive behavior, and controlled release of actives.
[0004]
[0004] Several surfactant types and architectures can be used in formulating VES fluids, including anionic, cationic, and zwitterionic surfactants (see References 1-11, appendix). Formation of stable micelles with high temperature and brine stability is preferred. Surfactant compositions that form useful rheology at concentrations in the range of 3%-8% are considered cost-effective in demanding applications. The exact surfactant concentration often depends on the bottom hole temperature and the desired fluid viscosity. Furthermore, VES fluids can break down to water-like Newtonian viscosity upon exposure to liquid hydrocarbons or dilution with reservoir brine. Fine control of viscosity can be further achieved with "breakers" that are rationally introduced for control at certain stages of well completion operations. The effectiveness of VES and breaker control can be measured by conductivity testing and monitoring of retained permeability. This can be extended to monitoring the effects on fracture propagation length, well connectivity, and formation preservation, and can also be augmented by tracer analysis. Another important property monitored by VES and well completion operations is fluid loss characteristics. By pressurizing the fluid flow up to a layer of controlled permeability (simulated in a core-sweep experiment in the laboratory), the cumulative fluid volume entering the core can be measured as a function of time, and a relationship between the total fluid loss coefficient and permeability can be obtained.
[0005]
[0005] Besides HF applications, VES for well stimulation and completion applications is also important. The availability of various VES fluid systems is advantageous to accommodate different formation characteristics, base lithology, mineral composition, formation fluids (brine chemistry) and operations (e.g., different pumping configurations). Tight gas wells, unconventional wells, shale, coal seams, and wells with reverse capillary effect, including nearly irreducible water saturation and hydrocarbon saturation, require chemistry optimized for specific well conditions. Low productivity of both old and new wells can be promoted by stimulation and completion procedures, such as acid stimulation and the use of diverters. Here, VES stimulation fluids have the following advantages: 1) the use of a scavenging surfactant system, 2) formation non-toxicity (no polymeric residue or formation damage), 3) lower surface tension, 4) no need for biocides or clay control agents, 5) insensitivity to salinity, and 6) flowback fluids can be reused.
[0006]
[0006] Acid stimulation is preferred to optimize productivity in carbonate reservoirs (calcite and dolomite). When production is reduced as a result of formation damage or low natural permeability, acid well stimulation can increase productivity by creating a more conductive flow path between the reservoir and the borehole. Stimulation methods in carbonate continuous formations are classified into two main groups: matrix treatment and acid fracturing treatment. Matrix stimulation using VES fluids involves pumping acid, solvents, or other treatment chemicals into the formation below the reservoir fracturing pressure. When acid is introduced into the carbonate formation, some of the minerals in the rock dissolve, which creates intricate high permeability channels or wormholes. Matrix treatment is often applied in zones with good natural permeability to avoid damage near the wellbore area. Acid fracturing stimulation, on the other hand, is performed above the fracturing pressure of the formation. A viscous pad (fracturing fluid without proppant) is pumped into the formation at a pressure above the fracturing initiation pressure, which fractures the rock. An acid stage is then pumped to etch the fracture surface. The acid also forms conductive wormholes at or near the fracture surface. After stimulation, the fractures close, but the increased conductivity between the formation and the wellbore is maintained due to the etching and the formation of the wormholes. In carbonate reservoirs, hydrochloric acid (HCl) is the most commonly applied stimulation fluid. Organic acids such as formic or acetic acid are used to acidify sandstone or carbonate formations, primarily in acid inhibition systems or in high temperature applications.
[0007]
[0007] Diversion is a technique used in injection treatments such as matrix stimulation to ensure uniform distribution of treatment fluid over the treatment interval. Injected fluids tend to flow along the path of least resistance, which results in poor treatment in the least permeable areas within the stimulation interval.
[0008]
[0008] Diversion techniques can be used to focus treatment in areas that require more stimulation. To be effective, the diversion effect should be temporary so that full productivity of the well can be restored when treatment is completed. There are two main categories of diversion: mechanical and chemical. Focusing on the use of chemical diversion, polymer-based fluids have been used, but VES-based fluids are of great interest due to their advantages in reducing resistance and preventing formation damage. In long-distance wells, coiled tubing (CT) is used to deliver the treatment fluid to the reservoir. The treatment fluid may consist of a VES fluid composition (3-10%) in 20-28% HCl with corrosion inhibitors.
[0009]
[0009] Prior art and patents on VES in general have been previously reported, including the following: 1. Principle of VES fluid formation: Worm-like micelles at higher concentrations 2. VES Fluid Investigation Method 3. Stimulus-response properties of VES fluids 4. Stability of VES fluid 5. Different material classes of VES fluids
[0010]
[0010] Patents related to oil field chemical applications: 1. Hydraulic fracturing fluids 2. Finishing Fluid 3. Stimulating fluid 4. IOR 5. Enhanced Oil Recovery (EOR)
[0011]
[0011] Patents by Schlumberger, Halliburton, Baker Hughes and BJ Services are common.
[0012]
[0012] Reports of highly stable VES fluids using acid matrices or media are silent on many of the particle, nanoparticle additives, nanocellulose components, for example.
[0013]
[0013] There have been no reports on the use of modified nanoparticles and nanomaterials in VES fluids in oilfield stimulation and matrix acid treatment.
[0014]
[0014] There is scope for reporting improved properties including stimuli-responsive properties of VES fluids, as well as effects such as self-diverting, controlled pH change, controlled dissolution, and higher temperature capabilities.
[0015]
[0015] These patents, applications, and publications that may be considered include the following: US Patent Number: US7,992,640B2 August 2011 Applicant Tianping Huang (Baker Hughes Inc.) ORGANIC ACID TREATING FLUIDS WITH VISCOELASTICSURFACTANTS AND INTERNAL BREAKERS US Patent Number: US7,303,019B2 December 2007 Applicant: Thomas Welton (Halliburton Energy Services) VISCOELASTIC SURFACTANT FLUIDS AND ASSOCATED DIVERTING METHODS US Patent Number: US7,159,659B2 January 2007 Applicant: Thomas Welton (Halliburton Energy Services) VISCOELASTIC SURFACTANT FLUIDS AND ASSOCATED ACDIZING METHODS US Patent Number: US7,159,659B2 October 2006 Applicant: QI Qu (BJ Services) ACID DIVERTING SYSTEM CONTAINING QUATERNARY AMINE US Patent Application Number: US2005 / 0126786A1 June 2005 Applicant: Diankui Fu (Schlumberger Technology Corporation) VISCOELASTIC ACID US Patent Application Number: US2010 / 0331223A1 December 2010 Applicant: Leiming Li (Schlumberger Technology Corporation) ACID VISCOSITY ENHANCER FOR VISCOELASTIC SURFACTANTS US Patent Application: US2014 / 0246198A1 September 2014 Applicant: Nisha Pandya (Halliburton Energy Services) BRANCHED VISCOELASTIC SURFACTANT FOR HIGH TEMPERATURE ACIDIZING US Patent Application: US2011 / 0152135A1 June 2011 Applicant: Yiyan Chen (Schlumberger) VISCOELASTIC SURFACTANT ACID TREATMENT US Patent Application: US2006 / 0118302A1 June 2006 Applicant: Michael Fuller (Schlumberger) SELF DIVERTING MATRIX ACID US Patent Application: US2013 / 0274.149A1 October 2013 Applicant: Valerie Lafitte (Schlumberger) FLUIDS AND METHODS INCLUDING NANOCELLULOSE Accompanying patents and patent applications US Patent Number: US2015 / 0072902A1 March 2015 Applicant: Thomas Welton (Schlumberger Technology Corporation) FLUIDS AND METHODS INCLUDING NANOCELLULOSE Summary of the Invention [Problem to be solved by the invention]
[0016] 1. New formulation: To develop and investigate the effectiveness of new viscoelastic surfactant (VES) formulations containing nanostructured composites as thickening additives for finishing and stimulating fluid applications. This involves modification of VES formulations with either: a) nanomaterial composites, b) polymer surfactant composites, c) thickening polymers, and d) modified polymer and nanomaterial additives. This action results in a) stimuli-responsive properties or control, b) better stability at higher temperatures and brine concentrations, and c) cost effectiveness and performance.
[0017] 2. Formulation optimization: Physicochemical characterization and standardized test methods should be performed to determine the best properties of these new VES compositions (nanomaterials and polymer composites) for structure-composition-property relationships. This includes characterization of formulation stability, viscosity measurements, rheology, and high-temperature rheology for various concentrations, leading to the demonstration of the advantages of cost-effectiveness or low-cost / high-performance ratio. Differentiation from existing VES formulations should be observed in the addition of superior properties and functionality. Other additives that provide improved additional functionality may include scale inhibitors, biocides, corrosion inhibitors, trace, fluid loss agents, layer stabilizers, and stimuli-responsive properties. The use of cellulose nanocrystals (CNCs), also called nanocellulose, as an additive is of great interest, especially due to its renewable and sustainable nature. The ability of nanocellulose materials to complex with VES fluids will be of great interest in enhancing the stability of worm-like micelles and in differentiation from other nanofiber interactions. For example, CNCs and nanofibers may affect the stability of the shear rate properties at higher temperatures of the VES.
[0018]
[0018] 3. Acid stimulating formulation: To develop novel VES and nanostructured composites as thickening media for acid stimulation, acid fracturing and diversion applications. Differentiation from existing reported VES formulations under highly acidic conditions is achieved by incorporating a) polyelectrolyte complexes, b) polymer-surfactant complexes, and c) nanomaterial additives, resulting in a) stimuli-responsive properties (e.g., self-diverting properties), b) higher stability at high temperatures and brine concentrations, and c) cost-effective performance. While common surfactants can be used, it is important to explore cationic, anionic, and zwitterionic groups for various counterions. The addition of nanomaterials and polymers may further improve these formulation performance. Surface modification with various silanes (sulfonate, carbonate, epoxy, amine, etc.) and application of polymer grafting by surface initiated polymerization (SIP) are new. Demonstration will include determining the use of various organic counterions to surfactants suitable for acidic conditions and will include testing for calcite / dolomite mineral type analogue dissolution. Specifications for viscosity, viscoelastic behavior, T and P stability, pH stability, and brine stability will be determined.
[0019] 4. Further optimization of the formulation with synergistic additives: To further explore the optimized properties of these new VES composites (polymers and nanoparticles) in terms of structure-composition-property relationships for acid challenge, fracturing, and diversion, additives for corrosion, scale, fluid loss prevention, etc. This includes physicochemical characterization and standardized test methods with other additives that provide enhanced additional functionality including scale inhibitors, biocides, corrosion inhibitors, trace, fluid loss agents, layer stabilizers, and stimuli-responsive properties. [Means for solving the problem]
[0020]
[0020] The present inventor conducted intensive research to solve the above-mentioned problems, and as a result, discovered that the above-mentioned problems can be solved by combining a viscoelastic surfactant with a modified nanomaterial, thereby completing the present invention.
[0021]
[0021] More specifically, the present invention is as follows.
[0022] 1. Viscoelastic surfactants, and modified nanomaterials, A composition for oil or gas well formation.
[0023] 2. The composition of claim 1, wherein the modified nanomaterial comprises nanocellulose.
[0024] 3. The composition according to item 1 or 2, wherein the modified nanomaterial has on its surface at least one selected from the group consisting of sulfate groups, sulfite groups, carboxy groups, ethylene oxide chains, amino groups, ester groups, silane groups and tertiary ammonium groups.
[0025] 4. The composition of claim 3, wherein the modified nanomaterial has sulfate groups on its surface.
[0026] 5. A composition described in any one of claims 1 to 4, wherein the modified nanomaterial has a grafted polymer on its surface.
[0027] 6. The composition according to any one of claims 1 to 5, further comprising a counterionic compound having a counterionic moiety for the ionic group of the viscoelastic surfactant.
[0028] 7. The composition of claim 6, wherein the counterion compound comprises an organic acid salt.
[0029] 8. The composition according to item 6 or 7, wherein the counter ionic compound comprises at least a carboxylate or a sulfonate.
[0030] 9. The composition according to any one of items 6 to 8, wherein the viscoelastic surfactant comprises at least one selected from the group consisting of cationic surfactants, anionic surfactants, zwitterionic surfactants and amphoteric surfactants.
[0031] 10. A viscoelastic surfactant having the formula (1): R 1 -N(R 2 )3 + X - (1) (In the formula, R 1 is an aliphatic group having 10 to 20 carbon atoms, R 2 is an aliphatic group having 1 to 6 carbon atoms, and X - The composition according to any one of items 6 to 9, comprising a compound represented by the formula:
[0032] 11. The composition according to any one of the preceding claims, further comprising a polymer and / or an additive.
[0033] 12. The composition according to item 11, wherein the polymer comprises at least one selected from the group consisting of polyacrylamide, poly(allylamine hydrochloride), poly(ethylene glycol), polyethyleneimine polyvinyl alcohol, poly(4-styrenesulfonic acid-co-maleic acid), polyvinylpyrrolidone, polyallylamine, and poly(diallyldimethylammonium), polyaniline, poly(4-vinylpyridine), polyaniline emeraldine.
[0034] 13. The composition according to claim 1, further comprising a solvent.
[0035] 14. A method of producing a composition, comprising: The method includes the step of combining a modified nanomaterial and a viscoelastic surfactant.
[0036] 15. A method of forming an oil or gas well, comprising: The method includes preparing a fluid including a solvent, a viscoelastic surfactant, a modified nanomaterial, and an acid material, and introducing the fluid into a well. Effect of the Invention
[0037]
[0022] According to the present invention, a composition for forming an oil well or gas well having excellent stability and self-diverting acid properties, a method for producing the composition, and a method for forming an oil well or gas well can be provided. [Brief description of the drawings]
[0038] [Figure 1] FIG. 1 is a diagram showing the acid sensitivity of viscoelastic surfactants in Example 1 and Comparative Example 1. [Diagram 2] FIG. 1 shows a HCl consumption test in comparison of Example 1 and Comparative Example 1. [Diagram 3]FIG. 1 is a diagram showing an HCl consumption test and the appearance of the samples in comparison with Examples 4 to 5 and Comparative Example 1. [Figure 4] FIG. 1 shows a HCl consumption test in comparison of Example 4 and Comparative Example 1. [Diagram 5] FIG. 1 shows potential viscoelastic surfactants. [Figure 6] FIG. 1 shows an HCl consumption test for comparison between Examples 6 to 8 and Comparative Example 2. [Figure 7] FIG. 1 shows an HCl consumption test in comparison with Examples 9 to 11 and Comparative Example 3. [Figure 8] FIG. 1 shows a comparison of HCl consumption tests for Examples 9, 11, 12 and Comparative Example 3. [Figure 9] FIG. 1 shows potential modifiers. [Figure 10] FIG. 1 shows the TGA results of CNC-APTES and CNC-AEAPTMS. [Figure 11] FIG. 1 shows the scheme of CNC modification and the FTIR and TGA results of cationic-CNCs. [Figure 12] Figure 1 shows the FTIR and TGA results of PDMEAMA-grafted CNCs. [Figure 13] FIG. 1 shows FTIR of PPEGMEMA grafted CNCs. [Figure 14] FIG. 1 is a graph showing the difference in viscosity between temperatures in a comparison of Examples 13 to 16. [Figure 15] FIG. 1 shows additive candidates. [Figure 16] FIG. 1 shows a comparative HCl consumption test for Examples 17 to 22. [Figure 17] FIG. 1 shows a comparative HCl consumption test for Examples 19 to 22. [Figure 18] FIG. 1 shows a HCl consumption test in comparison of Examples 23-25 and 31 and Comparative Examples 4-6 and 12. [Figure 19] FIG. 1 shows a HCl consumption test in comparison of Examples 26-28 and 31 and Comparative Examples 7-9 and 12. [Figure 20] FIG. 1 shows an HCl consumption test for comparison between Examples 29 to 31 and Comparative Examples 10 to 12. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039]
[0024] Hereinafter, an embodiment of the present invention (hereinafter also referred to as "the present embodiment") will be described in detail. The embodiments described below are provided merely to illustrate the present invention. The present invention is not limited to these embodiments.
[0040]
[0025] 1. Composition for forming oil or gas wells The oil or gas well formation composition in this embodiment includes a viscoelastic surfactant and a modified nanomaterial. The composition has excellent self-diverting acid properties and stability.
[0041]
[0026] As described in the Examples section, the viscosity of the composition changes based on the acid concentration or pH. The viscosity of the composition can be controlled by supplying acid or consuming acid. The term "self-diverting acid characteristic" in the present disclosure means a characteristic of changing viscosity based on acid (see Figures 5 and 6, etc.). In particular, for oil or gas well formation, the rate of change of viscosity is preferably large.
[0042]
[0027] As described in the Examples section, it is preferred that the self-diverting acid property is maintained at various pH or temperature. In particular, for oil or gas well formation, the composition is exposed to various pH or temperature. The term "stable" in the present disclosure means that the self-diverting acid property is maintained at various pH or temperature.
[0043] 1.1. Viscoelastic surfactants Examples of viscoelastic surfactants include, but are not limited to, at least one selected from the group consisting of cationic surfactants, anionic surfactants, zwitterionic surfactants and amphoteric surfactants. Viscoelastic surfactants include ionic groups. Viscoelastic surfactants may be used alone or in combination of two or more thereof.
[0044] Examples of such ionic group include, but are not limited to, positively charged groups such as ammonium groups, and negatively charged groups such as carboxylic acid, sulfonic acid, sulfate, phosphonate, etc. Among them, ammonium groups, carboxylic acid and sulfonic acid are preferred, and at least one selected from the group consisting of carboxylic acid and sulfonic acid is more preferred. By using such viscoelastic surfactant, self-diverting acid property and stability tend to be improved.
[0045]
[0030] 1.1.1. Cationic surfactant Cationic surfactants have a group that carries a positive charge. Examples of such cationic surfactants include, but are not limited to, alkyl amines, alkyl diamines, alkyl ether amines, alkyl quaternary ammonium, dialkyl quaternary ammonium, and alkyl ester quaternary ammonium.
[0046]
[0031] Some of such cationic surfactants include, but are not limited to, those represented by the following formula (1): R 1 -N + (R 2 )3X - (1) (In the formula, R 1 represents alkyl, alkenyl, cycloalkyl, arylalkyl, alkylaryl, alkylarylalkyl, alkyletheralkyl, alkylaminoalkyl, alkylamidoalkyl, or alkylesteralkyl; R 2 each independently represents an alkyl, an alkenyl, or a cycloalkyl; X -is an anion).
[0047]
[0032] R 1 The number of carbon atoms in the group represented by R is preferably 8 to 30, and more preferably 10 to 20. 1 may be a straight chain, branched or cyclic structure. 1 preferably represents an aliphatic group, such as alkyl, alkenyl, cycloalkyl, arylalkyl, alkylaryl, and alkylarylalkyl.
[0048]
[0033] R 2 The number of carbon atoms in the group represented by R is preferably 1 to 20, and more preferably 1 to 6. 2 may be a straight chain, branched or cyclic structure. 2 preferably represents an aliphatic group, such as alkyl.
[0049]
[0034] X 1 The anion represented by the formula (I) is as described above. Among them, organic anions and halogen ions are preferred, and halogen ions are more preferred.
[0050]
[0035] Among these, cetyltrimethylammonium bromide (CTAB) represented by the following formula is preferred.
[0051] [ka]
[0052]
[0036] 1.1.2. Anionic surfactants Anionic surfactants have a negatively charged group. Examples of such anionic surfactants include, but are not limited to, alkyl carboxylates, alkyl ether carboxylates, alkyl sulfates, alkyl ether sulfates, alkyl sulfonates, alkyl ether sulfonates, alkyl sulfates, alkyl ether sulfates, alkyl phosphates, and alkyl ether phosphates.
[0053]
[0037] Some of such anionic surfactants include, but are not limited to, those represented by the following formula (2): RZ (2) wherein R represents alkyl, alkenyl, cycloalkyl, arylalkyl, alkylaryl, alkylarylalkyl, alkyletheralkyl, alkylaminoalkyl, alkylamidoalkyl, or alkylesteralkyl, and Z represents a group having a negative charge.
[0054]
[0038] The number of carbon atoms in the group represented by R is preferably 8 to 30, and more preferably 10 to 20. 1 R may be a linear, branched, or cyclic structure. Among other things, R preferably represents an aliphatic group, such as alkyl, alkenyl, cycloalkyl, arylalkyl, alkylaryl, and alkylarylalkyl.
[0055]
[0039] Z represents the negatively charged hydrophilic head of the surfactant. Examples of negatively charged groups represented by Z include, but are not limited to, carboxylate COO - , sulfonate SO3 - , Sulfate SO4 - , phosphonates, phosphates, and combinations thereof.
[0056] 1.1.3. Zwitterionic surfactants Zwitterionic surfactants are associated with both negative and positive moieties. Examples of such zwitterionic surfactants include, but are not limited to, alkyl betaines, alkyl amido betaines, alkyl amino oxides, and alkyl quaternary ammonium carboxylates.
[0057]
[0041] Some of such zwitterionic surfactants include, but are not limited to, those represented by the following formula (3): R 1 -N + (R 2 )2R 3 Z (3) (wherein R represents alkyl, alkenyl, cycloalkyl, arylalkyl, alkylaryl, alkylarylalkyl, alkyletheralkyl, alkylaminoalkyl, alkylamidoalkyl, or alkylesteralkyl; R 2 each independently represents an alkyl, alkenyl, or cycloalkyl; R 3 represents alkenyl, and Z represents a group having a negative charge.
[0058] R, R 2 and Z are the same as above. 3 The number of carbon atoms in the group represented by R is preferably 1 to 20, and more preferably 1 to 6. 3 may be a straight chain, branched, or cyclic structure.
[0059]
[0043] Among these, the following zwitterionic surfactants are preferred:
[0060] [ka]
[0061]
[0044] 1.1.4. Amphoteric surfactants Amphoteric surfactants have both positively charged and negatively charged portions in a certain pH range. Amphoteric surfactants also have only negatively charged portions in a certain pH range (e.g., typically slightly alkaline), and only positively charged portions in a different pH range (e.g., typically slightly acidic). Examples of such amphoteric surfactants include, but are not limited to, the following formula (4): R 1 -NH + (R 2 )R 3 COO - (4) (In the formula, R 1 is an aliphatic group having 10 to 20 carbon atoms, R 2 and R 3 is an aliphatic group having 1 to 6 carbon atoms.
[0062] 1.1.5. Viscoelastic surfactant content The content of the viscoelastic surfactant is preferably 0.1% by weight or more, 0.5% by weight or more, 1.0% by weight or more, 1.5% by weight or more, or 2.0% by weight or more. When the content of the viscoelastic surfactant is 0.1% by weight or more, the self-diverting acid property tends to be improved.
[0063]
[0046] The content of the viscoelastic surfactant is preferably 30% by weight or less, 20% by weight or less, 10% by weight or less, 7.5% by weight or less, or 5.0% by weight or less based on the total weight of the composition. When the content of the viscoelastic surfactant is 90% by weight or less, the stability tends to be improved.
[0064]
[0047] When the viscoelastic surfactant is used in combination of two or more kinds, the above content of the viscoelastic surfactant is the total amount thereof.
[0065] 1.2. Counterion Compound The composition may further comprise a counter-ion compound having a counter-ion moiety for the ionic group of the viscoelastic surfactant.When the viscoelastic surfactant is a cationic surfactant, the counter-ion compound means an anionic compound.Furthermore, when the viscoelastic surfactant is an anionic surfactant, the counter-ion compound means a cationic compound.Furthermore, when the viscoelastic surfactant is a zwitterionic surfactant or an amphoteric surfactant, the counter-ion compound means a cationic compound and / or an anionic compound.
[0066]
[0049] Examples of such counter ion compounds include, but are not limited to, inorganic counter ion compounds and organic counter ion compounds. Among them, organic counter ion compounds are preferred. By using such counter ion compounds, self-diverting acid properties and stability tend to be improved.
[0067]
[0050] Inorganic counterion compounds include, but are not limited to, alkali metal inorganic salts such as sodium chloride and potassium bromide, and alkaline earth metal inorganic salts such as calcium chloride.
[0068]
[0051] Organic counterion compounds include, but are not limited to, aliphatic carboxylic acids; alicyclic carboxylic acids; aromatic carboxylic acids such as benzoates, salicylates, naphthalene carboxylates, naphthalene dicarboxylates; aliphatic sulfonic acids, alicyclic sulfonic acids, aromatic sulfonic acids such as benzenesulfonates, alkylbenzenesulfonates, naphthalenesulfonates; aliphatic alcohols; alicyclic alcohols; aromatic alcohols such as phenols, naphthols; aliphatic amines; alicyclic amines; and aromatic amines.
[0069]
[0052] Among them, organic acids, such as aromatic carboxylic acids and aromatic sulfonic acids, are preferred, and sodium salicylate and sodium dodecylbenzenesulfonate are more preferred.By using such counter ion compounds, self-diverting acid properties and stability tend to be improved.
[0070] 1.3. Modified Nanomaterials The term "nanomaterial", as used in this disclosure, is intended to include any suitable known nanoscale material having nanoscale size in at least one dimension. Examples of such modified nanomaterials include, but are not limited to, nanocellulose, carbon nanotubes, graphene, nanofibers, nanoclays such as silicates, particles such as silica nanoparticles, modified silica nanoparticles, titanium oxide nanoparticles. The modified nanomaterials may be used alone or in combination of two or more thereof. The shape of the nanomaterial may be spheres, whiskers, or fibers.
[0071]
[0054] Among them, nanocellulose and nanoclay are preferred, and nanocellulose is more preferred.Nanocellulose is also called cellulose nanofiber (CNF), microfibrillated cellulose (MFC) or cellulose nanocrystal (CNC).By using nanocellulose, self-diverting acid property and stability tend to be improved.
[0072]
[0055] The terms "modified" or "functionalized" as used in this disclosure mean that a nanomaterial has functional groups and / or grafted polymers introduced onto its surface.
[0073]
[0056] Examples of such functional groups include, but are not limited to, at least one selected from the group consisting of a sulfate group, a sulfite group, a carboxy group, an ethylene oxide chain, an amino group, an ester group, a silane group, and a tertiary ammonium group.
[0074]
[0057] Among them, ionic group is preferred, sulfate group, carboxy group, amino group and silane group are more preferred, sulfate group, carboxy group are more preferred, and sulfate group is even more preferred. By using nanocellulose having such groups on its surface, self-diverting acid property and stability tend to be improved.
[0075]
[0058] Examples of such graft polymers include, but are not limited to, poly(meth)acrylic acid, poly(methyl)methacrylate, poly(ethyl)methacrylate, poly(propyl)methacrylate, poly(butyl)methacrylate, poly(benzyl)methacrylate, poly(cyclohexyl)methacrylate, poly(2-hydroxyethyl)methacrylate, poly(2-hydroxypropyl)methacrylate, poly(polyalkylene glycol (meth)acrylate), poly(alkoxypolyalkylene glycol (meth)acrylate), poly(diethylaminoethyl (meth)acrylate), poly(dimethylaminoethyl (meth)acrylate), polyacrylamide, N,N-dimethyl(meth)acrylamide, polyalkylene glycol.
[0076]
[0059] Among them, poly(poly(ethylene glycol) methyl ether methacrylate), poly(2-(dimethylamino) ethyl methacrylate) are preferred. The use of nanocellulose having such graft polymers on its surface tends to improve the self-diverting acid properties and stability.
[0077]
[0060] The content of the modified nanomaterial is preferably 0.01 wt% or more, 0.05 wt% or more, 0.1 wt% or more, 0.2 wt% or more, or 0.3 wt% or more. When the content of the modified nanomaterial is 0.05 wt% or more, the self-diverting acid property tends to be improved.
[0078]
[0061] The content of the modified nanomaterial is preferably 20% by weight or less, 10% by weight or less, 5.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less based on the total amount of the composition. When the content of the modified nanomaterial is 20% by weight or less, the stability tends to be improved.
[0079]
[0062] The weight ratio of the viscoelastic surfactant to the modified nanomaterial is preferably 1.0 times or more, 2.0 times or more, 3.0 times or more, 4.0 times or more. When the weight ratio of the viscoelastic surfactant to the modified nanomaterial is 1.0 times or more, the self-diverting acid property tends to be improved.
[0080]
[0063] The weight ratio of the viscoelastic surfactant to the modified nanomaterial is preferably not more than 20 times, not more than 15 times, or not more than 10 times. If the weight ratio of the viscoelastic surfactant to the modified nanomaterial is not more than 20 times, the stability tends to decrease.
[0081] 1.4. Polymers The composition may further include a polymer if necessary. Examples of the polymer include, but are not limited to, at least one selected from the group consisting of polyacrylamide, poly(allylamine hydrochloride), poly(ethylene glycol), polyethyleneimine, polyvinyl alcohol, poly(4-styrenesulfonic acid-co-maleic acid), polyvinylpyrrolidone, polyallylamine, poly(diallyldimethylammonium), polyaniline, poly(4-vinylpyridine), and polyaniline emeraldine. Furthermore, the polymer includes a polyelectrolyte.
[0082]
[0065] Among them, the polymer containing nitrogen atom is preferred.As such additive polymer, polyacrylamide, poly(allylamine hydrochloride), polyvinyl alcohol, poly(4-styrenesulfonic acid-co-maleic acid), polyvinylpyrrolidone, polyallylamine, poly(diallyldimethylammonium), polyaniline, poly(4-vinylpyridine) and polyaniline emeraldine are more preferred.By using such polymer, self-diverting acid property and stability tend to be improved.
[0083]
[0066] The content of the polymer is preferably 0.1% by weight or more, 0.2% by weight or more, or 0.3% by weight or more. When the content of the polymer is 0.5% by weight or more, the self-diverting acid property tends to be improved.
[0084]
[0067] The content of the polymer is preferably 10% by weight or less, 7.5% by weight or less, or 5% by weight or less based on the total amount of the composition. When the content of the polymer is 10% by weight or less, the stability tends to be improved.
[0085] 1.5. Additives The composition may further include additives as necessary. Examples of additives include, but are not limited to, at least one selected from the group consisting of scale inhibitors, biocides, corrosion inhibitors, tracers, fluid loss agents, layer stabilizers, and stimuli-responsive property agents. The additives may be used alone or in combination of two or more thereof.
[0086] 1.6. Solvent The composition may further include a solvent as needed. Examples of the solvent include, but are not limited to, water. The composition may include water as a brine.
[0087]
[0070] The content of the solvent is preferably 30% by weight or more, 40% by weight or more, 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more.The content of the solvent is preferably 97% by weight or less, 95% by weight or less, 90% by weight or less, 80% by weight or less, 70% by weight or less, 60% by weight or less based on the total amount of the composition.When the content of the solvent is within the above range, the self-diverting acid property and stability tend to be improved.
[0088] 1.7. Other Ingredients The composition may further include other components as required, examples of which include, but are not limited to, acid materials such as HCl, HF, and the like.
[0089]
[0072] As mentioned above, the viscosity of the composition changes based on the acid concentration or pH. The viscosity of the composition can be controlled by supplying acid or consuming acid. Therefore, when the composition contains acid, the concentration of the acid is not limited. From the viewpoint of self-partitioning acid property and stability, the concentration range of the acid is preferably 0.1-40 wt%.
[0090]
[0073] 1.8. Viscoelastic properties 1.8.1 Acid Sensitivity of the Composition The viscosity of the composition at a specified temperature decreases with increasing acid concentration. The ratio of the viscosity of a composition containing 4% by weight of acid at 25°C to the viscosity of a composition containing 20% by weight of acid at 25°C is preferably 25 to 50, 30 to 45, or 30 to 40.
[0091]
[0074] 25°C, 58S for each acid concentration of the composition -1 The preferred viscosity ranges are as follows: The viscosity of a composition containing 4 wt % of acid at 25° C. is preferably 500 to 1000 cP, 525 to 900 cP, or 550 to 800 cP. The viscosity of a composition containing 8 wt % of acid at 25° C. is preferably 450 to 1000 cP, 475 to 900 cP, or 500 to 800 cP. The viscosity of a composition containing 12% by weight of acid at 25° C. is preferably 200 to 400 cP, 225 to 375 cP, or 250 to 350 cP. The viscosity of a composition containing 16% by weight of acid at 25° C. is preferably 50 to 250 cP, 75 to 225 cP, or 100 to 200 cP. The viscosity of a composition containing 20% by weight of acid at 25° C. is preferably 1 to 100 cP, 1 to 75 cP, or 1 to 50 cP.
[0092]
[0075] The ratio of the viscosity of a composition containing 4 wt% acid at 40°C to the viscosity of a composition containing 20 wt% acid at 25°C is preferably 25-50, 30-45, or 30-40.
[0093]
[0076] 40°C, 58S for each acid concentration of the composition -1 The preferred viscosity ranges are as follows: The viscosity of a composition containing 4% by weight of acid at 40° C. is preferably 500 to 1000 cP, 525 to 900 cP, or 550 to 800 cP. The viscosity of a composition containing 8 wt % of acid at 40° C. is preferably 450 to 1000 cP, 475 to 900 cP, or 500 to 800 cP. The viscosity of a composition containing 12% by weight of acid at 40° C. is preferably 200 to 400 cP, 225 to 375 cP, or 250 to 350 cP. The viscosity of a composition containing 16% by weight of acid at 40° C. is preferably 30 to 200 cP, 40 to 175 cP, or 50 to 150 cP. The viscosity of a composition containing 20% by weight of acid at 40° C. is preferably 1 to 100 cP, 1 to 75 cP, or 1 to 50 cP.
[0094]
[0077] The ratio of the viscosity of a composition containing 4 wt% acid at 50°C to the viscosity of a composition containing 20 wt% acid at 25°C is preferably 25-50, 30-45, or 30-40.
[0095]
[0078] 50°C, 58S for each acid concentration of the composition -1 The preferred viscosity ranges are as follows: The viscosity of a composition containing 4 wt % of acid at 50° C. is preferably 250 to 700 cP, 275 to 550 cP, or 300 to 400 cP. The viscosity of a composition containing 8 wt % of acid at 50° C. is preferably 250 to 700 cP, 275 to 550 cP, or 300 to 500 cP. The viscosity of a composition containing 12% by weight of acid at 50° C. is preferably 60 to 250 cP, 80 to 225 cP, or 100 to 200 cP. The viscosity of a composition containing 16% by weight of acid at 50° C. is preferably 30 to 200 cP, 40 to 175 cP, or 50 to 150 cP. The viscosity of a composition containing 20% by weight of acid at 50° C. is preferably 1 to 100 cP, 1 to 75 cP, or 1 to 50 cP.
[0096] 1.8.2. Acid consumption test The composition has self-diverting acid properties, which can be illustrated by an acid consumption test: as acid is consumed by reaction with calcium carbonate or other reactive minerals, the viscosity of the composition increases.
[0097]
[0080] The ratio of the viscosity at 25°C of a composition having consumed 12% by weight of an acid to the viscosity at 25°C of a composition having consumed 4% by weight of an acid is preferably 20-60, 25-55, or 30-50.
[0098]
[0081] The ratio of the viscosity at 25°C of a composition having consumed 18% by weight of acid to the viscosity at 25°C of a composition having consumed 12% by weight of acid is preferably 0.016 to 0.05, 0.018 to 0.04, or 0.02 to 0.03.
[0099]
[0082] 25°C, 58S for each consumed acid of the composition -1 The preferred viscosity ranges are as follows: The viscosity of the composition having consumed 4% by weight of acid at 25° C. is preferably 1 to 100 cP, 1 to 75 cP, or 1 to 50 cP. The viscosity of the composition containing 8% by weight of acid at 25° C. is preferably 250 to 700 cP, 275 to 550 cP, or 300 to 500 cP. The viscosity of the composition having consumed 12% by weight of acid at 25° C. is preferably 500 to 1000 cP, 525 to 900 cP, or 550 to 800 cP. The viscosity of the composition having consumed 16% by weight of acid at 25° C. is preferably 300 to 800 cP, 350 to 700 cP, or 400 to 600 cP. The viscosity of the composition having consumed 18% by weight of acid at 25° C. is preferably 1 to 100 cP, 1 to 75 cP, or 1 to 50 cP.
[0100] 2. Method for Producing the Composition The method for producing the composition includes mixing the modified nanomaterial and the viscoelastic surfactant. In the mixing step, other ingredients may be mixed as necessary.
[0101] The mixing step may include the following steps in the following order: mixing the modified nanomaterial with a solution to obtain solution A; adding a polymer, additive, acid and / or solution to solution A to obtain solution B; adding a viscoelastic surfactant to solution B to obtain solution C. Additionally, the mixing step may include adding a counter ion compound, such as sodium salicylate, to solution C.
[0102]
[0085] The mixing method in the mixing step is not particularly limited, and any process known in the art may be applied. Examples of such methods include mechanical mixing methods such as vortexing, and ultrasonic treatment.
[0103] 3. Method for forming an oil or gas well A method of forming an oil or gas well includes preparing a fluid including a solvent, a viscoelastic surfactant, a modified nanomaterial, and an acid material, and introducing the fluid into the well.
[0104]
[0087] Furthermore, the method of forming an oil or gas well may further include a step of supplying an acid to the fluid introduced into the well. The fluid containing the composition consumes or consumes the acid to react with minerals such as calcite or dolomite. The fluid can continue to form the well by the acid supply step.
[0105] 4. Summary This disclosure involves the development of high performance and functional thickening chemicals based on viscoelastic surfactants (VES) for well stimulation and completion applications. This includes acid well stimulation, formation control and diversion to form high permeability and conductive pathways in wells. By focusing on acid or acid-treated formulations, the stability of VES for various concentrations and compositions in the presence of brine, controlled pressure and temperature, and its effect on viscosity or rheology were tested. Formulations included the addition of nanocellulose, polymers, nanoparticles, and other additives to enhance performance and functionality towards cost effectiveness. This included modification of particles and additives by salification and grafting of polymers. Complexation with polymers with additives was also performed. Testing included physicochemical determination of properties against various control colloidal formulations. Improvement and control of properties was evident with the resulting formulations, showing that the combination of cationic VES and nanocellulose (CNC) had superior performance. Modification with grafted or complexed colloidal polymer solutions also enabled stimuli-responsiveness. Higher stability of the cationic-VES-CNC composition was demonstrated over a number of brine, temperature, and pH conditions, which showed better acid stimulation properties compared to VES without modified additives. Results also supported the usefulness of acid stimulation over concentration with acid consumption tests, which showed self-diverting acid (SDA) behavior. Finally, higher temperature performance was observed along with stability of the VES-CNC over the control sample.
[0106] 4.1. The inventors have developed a thickening medium for completion and stimulation of oil / gas wells with high and low permeability and depth. This involves the preparation of acidified viscoelastic surfactant (VES) media based on cationic, anionic, zwitterionic and amphoteric surfactants with compatible counterion compounds that result in stable concentration-dependent viscous behavior at ambient to elevated temperatures. This is exemplified by the CTAB-NaSal or cetyltrimethylammonium bromide-sodium salicylate systems, as well as other combinations of surfactants and their counterion compounds. This phenomenon is based on the formation of more highly ordered worm-like micelles and their networked gel properties.
[0107] Additives can be formulated and combined with the VES-complex in a specific order to obtain stabilized colloidal solutions and thickened networked gels, resulting in higher stability and higher temperature properties. Additives can be based on particles, chemically surface modified particles, or small molecules resulting in nanostructured composites.
[0108] 4.3 Molecular and macromolecular additives can be formulated and combined with the VES-complex in a specific order to obtain stabilized colloidal solutions and thickened networked gels, resulting in higher stability and higher temperature properties. The additives are corrosion inhibitors, scale inhibitors, biocides, fluid loss agents, layer stabilizers, etc., to form complex fluids.
[0109] Specifically, silica nanoparticles, modified silica nanoparticles, nanoclay, cellulose-based nanoparticle materials can be added in a specific order in combination with cationic, anionic and zwitterionic compositions. Physicochemical characterization and standardized testing methods based on these optimized formulations provide higher stability and stimuli-responsive properties.
[0110] Specifically, polymeric materials based on polyelectrolytes, water-soluble polymers, and other polymers can be added in a specific order in combination with cationic, anionic, and zwitterionic compositions. Physicochemical characterization and standardized testing methods based on these optimized formulations provide higher stability and stimuli-responsive properties.
[0111] Specifically, nanoparticle materials based on nanocellulose (CNC) obtained from cellulose sources (wood pulp, cotton, agricultural waste, etc.) can be added in a specific order in combination with cationic, anionic and zwitterionic compositions. Physicochemical characterization and standardized testing methods based on these optimized formulations result in higher stability and stimuli-responsive properties.
[0112] Specifically, chemically and surface-modified nanoparticle materials based on nanocellulose (CNC) can be added in a specific order in combination with cationic, anionic and zwitterionic compositions. Physicochemical characterization and standardized testing methods based on these optimized formulations provide higher stability and stimuli-responsive properties.
[0113]
[0096] 4.8. Specifically, nanocellulose (CNC) based nanoparticle materials were added in a specific order in combination with cationic, anionic and zwitterionic compositions and showed stimuli-responsive properties along with diverting and self-diverting acid (SDA) properties, as well as good enhancement in disintegration of micelles upon most of the HCl being depleted.
[0114] 4.9. Specifically, nanoparticle materials based on nanocellulose (CNC) in combination with cationic, anionic and zwitterionic compositions have been reported, e.g., in the 100s. -1Rheometry performed at a shear rate of 100 psi, 400 psi and a temperature ramp of 10 F / min from 77 F (25° C.) to 350 F (176° C.) showed good improvement in stability and viscosity at higher temperatures.
[0115]
[0098] 4.10. Specifically, polymeric materials based on commercially obtained polymers complexed with CNCs in combination with cationic, anionic and zwitterionic compositions exhibited SDA properties with good viscosity enhancement and stimuli responsiveness at higher temperature stability.
[0116] Specifically, surface modified nanoparticles composited with CNCs by grafting polymers onto the surface in combination with cationic, anionic and zwitterionic compositions showed SDA properties with good viscosity enhancement and stimuli responsiveness at higher temperature stability.
[0117] 4.12. Surface modified nanoparticles complexed with CNCs by grafting of polymers to the surface, specifically in combination with cationic, anionic and zwitterionic compositions. Grafting includes 1) surface initiated polymerization (SIP) or "grafting from", 2) "grafting to or onto", and 3) "grafting through". Methods may also include chemisorption or physisorption. They showed SDA properties with good viscosity enhancement and stimuli responsiveness in stability at higher temperatures. EXAMPLES
[0118]
[0101] Hereinafter, the present invention will be described in more detail with reference to examples, but it should be understood that the scope of the present invention is in no way limited to these examples.
[0119]
[0102] 1. Control Experiment The present formulations of VES and acid challenge fluid compositions are specified and designated as controls or published patent compositions. This may be differentiated by the types of surfactants and other additives in the present formulation. It is important to specify the ratio or percentage of surfactants, counter ion compounds, and to determine the minimum percolation threshold for the desired properties. It should be possible to specify different types of surfactants, including the presence of any co-surfactants, solvents, and soluble salts.
[0120]
[0103] 2. Stability comparison The first step is to determine the stability of the fluid under acidic conditions of various pH. The acid consumption test simulates the ability of the VES formulation to react with the calcite and dolomite formations. Therefore, it is important to monitor the changes in the VES stability over time with various pH and temperature conditions.
[0121] 3. New Compositions Modification of the composition by counterion compounds, polymer complexes, and surfactant chemical structure. This includes determining the advantages of cationic, anionic, and zwitterionic surfactants. The fluids may contain two or more different surfactants, preferably anionic or nonionic surfactants, so that the reservoir rock is water wettable for better fluid mobility through the formation. Specific organic counterion compounds are used that are more suitable for acid stimulation conditions. Various surface modification protocols of additives with silanes (sulfonates, carbonates, epoxies, amines, etc.) or with polymer grafting provide acid stability and stimuli-responsive properties. Through careful design, these fluids are specially engineered to give viscosity, solubility, and temperature stability properties that are tailored to the specific stimulation application.
[0122] 4. Testing and Characterization Physicochemical characterization and experiments include: 1) Viscosity measurements of VES at various concentrations (1-10%) under different temperature and salt conditions. 2) Viscosity measurements for various pH and salt conditions. 3) Monitoring the decrease in viscosity with increasing shear rate in cp or Pas. 4) Rheological and viscoelastic properties. Tests are performed in comparison to a control additive of known or reported composition: a) rheology, b) stability with respect to T and P, c) stability with respect to pH and salt, d) flow conditions at controlled osmolarity, e) ability to act as a carrier for other additives (non-water soluble).
[0123]
[0106] Desired properties to be monitored include higher viscosity over a wide range of temperatures, especially at the upper end, and at low surfactant loadings to reduce costs. They should also be effective in many salt brines, including seawater, which is necessary to achieve formation stability. Maintenance of high viscosity at low pH and various salt conditions is important for acid stimulation and acid fracturing applications. Stimulus-response properties should also be observed - shift in peak dissolution rate, shift in viscosity versus concentration range, and shift in viscosity versus time.
[0124] 5. Polymer Compositions and Nanostructuring Polymer-surfactant complexes are generally more stable than small molecule surfactants. The addition of polymers, nanoparticles, and nanostructuring of the complexes requires: 1) To investigate the improved stability of polyelectrolyte-surfactant complexes and higher ordered micelles at specific concentrations. 2) To investigate the formation of stable complexes that exhibit stimuli-response and gradient properties (concentration dependence).
[0125] In particular, the addition of clay and silica nanomaterials, graphene nanoparticles, nanocellulose nanoparticles and nanofibers can provide better colloidal properties with micelle stability and minimum percolation threshold. The additives can provide stimuli-responsiveness, improved fluid loss prevention, increased corrosion resistance, and fluid stability under high T and P conditions. In-situ polymerized polymer-polyelectrolyte complexes or polymer-grafted nanoparticle complexes (surface modification) as new additives for VES fluids are possible.
[0126]
[0109] 6. Acid irritation and crushing properties After determining the stability of the formulated VES and nanomaterial-formulated VES at low pH (high acid content) and various salt concentrations, their ability to react with simulated formation minerals is investigated. Carbonate rock stimulation typically involves the reaction of acids with minerals such as calcite (CaCO3) or dolomite CaMg(CO3)2. The reaction rates with these minerals are observed by titration-type analysis under both ambient and pressurized conditions. Various acid concentrations are used, including 1-30 wt% HCl addition. Using viscosity and rheology measurements with temperature control, the change in viscosity is also monitored as a function of time.
[0127] 7. Main Protocols and Formulations Preparation of VES compositions of a particular surfactant (or with co-surfactant) and counter-ionic compound ranges in concentration from 1-10% by weight. This is done simply by adding the surfactant to water and brine or salt resulting in a translucent clear solution and increasing the viscosity (shear thinning). Mixing can be done manually and by use of a mechanical mixer or sonication. Once the VES solution is prepared, it can be tested for physicochemical properties including viscosity or rheology. Additionally, various compositions including polymers, nanomaterials and active substances (additives) are measured and measurements are repeated as well as benchmarked in previous control experiments. This has the potential to stabilize these micelles through complexes, which result in a stable network and fixation of micelles by orthogonal directional assembly.
[0128] 8. Example of Total Concentration Protocol Assuming a total of 100%, and using cetyltrimethylammonium bromide (CTAB) as an exemplary surfactant, the remainder of the composition is water. CTAB-VES1:CTAB(6wt%)+CaCl2(30wt%)+Water(64wt%) CTAB-VES2: CTAB (6 wt%) + sodium salicylate (0.5 wt%) + water (93.5 wt%) COMM-VES3: Commercial surfactant (6 wt%) + Na salicylate (1 wt%) + water (93 wt%), Commercial surfactant (6 wt%) + CaCl2 (30 wt%) + water (64 wt%) Assumes dilution from indicated wt% of commercial sample. CTAB-VES-Nano and CTAB: (Y wt%) + Na salicylate (0.5 wt%) + nano additives (X wt%) + water (93.5 wt%). CTAB-VES-POLY and CTAB: (Y wt%) + Sodium Salicylate (0.5 wt%) + POLY (X%) + Water (93.5 wt%) CTAB-VES-Active and CTAB: (Y wt%) + Sodium Salicylate (0.5 wt%) + Active (X wt%) + Water (93.5 wt%) Acidification: Adding various concentrations of HCl to adjust the pH Control: Commercial surfactant or polymer sample
[0129]
[0112] 9. Desired Properties Some of the characteristics that are monitored include: 1. Stability at various temperatures to maintain viscosity value and retain clarity or cloud point. Viscosity at cp (10x) ranges from 500 to 10sec1, decreasing with increasing shear rate or from 50 to 100°C. - Higher concentrations, addition of salts, and addition of alcohol co-surfactants are tolerated for stabilization. 2. Stable in fresh water or brine conditions to seawater (100,000-300,000ppm). 3. Stability at low pH conditions with added acid content of 1-20 wt%. 4. Stability of VES under various acidic conditions at higher pressures and temperatures as specified.
[0130] 10. Viscosity and Rheology Initial formulation: - Viscosity at various temperatures - Most of the temperature during acid stimulation is ambient. - Viscosity vs. time at constant temperature - Various concentrations: 3-10% VES, 5-15% HCl and HF, 5-15% NaCl, Mg or CaCl2, or buffer salts - pH from 0 to 7, viscosity measurement, various temperatures - 25 to 60°C. - Change in viscosity vs. the amount of HCl added (acid consumed) in the series - Increasing concentration over time. - Self-diverting acid (SDA) properties - Stages of various thickening properties with varying penetration rates - Permeability simulating calcite and sandstone formations
[0131]
[0114] 11. Data and Results The results of the studies relating to the methods used, as well as the compositions and conditions, are outlined in A-G.
[0132] The best results are as follows: The use of CTAB surfactants with added cationic-CNC and polymer-grafted CNC shows the best improvement in viscosity at room temperature and 60°C. CNC-polyvinyl alcohol or CNC-PVA premix solids (1:1) also provided viscosity improvement at higher temperatures. The self-diverting acid properties show stimuli-responsive behavior for all tests, resulting in the ability to shift dissolution properties with pH. Thus, the procedures and results summaries in each section A-G are used to support the claims in this patent application.
[0133] A) HCl Consumption Test of CTAB VES with Cellulose Nanocrystals (CNC): Typical preparation procedure for 12% HCl spent solution (20% max, 8% residual) The compositions were produced by mixing the components shown in Table 1. First, a master solution A of CNC was prepared by dissolving CNC in water and sonicating for 1 h. Then, hydrochloric acid, water, and CTAB were added to solution A in that order and vertex mixed until CTAB was completely dissolved to obtain solution B. Finally, NaSal solution was added to solution B and vertex mixed. A gel-like solution formed within seconds. The resulting solution was left to stand overnight to remove bubbles. The amount of HCl was adjusted based on the HCl concentration.
[0134]
[0117] The acid sensitivity of the composition is shown in Figure 1. In Figure 1, the vertical axis indicates viscosity, and the horizontal axis indicates the concentration of HCl added to the composition. Figure 1 (a) to (c) show the acid sensitivity at 25 to 60°C.
[0135]
[0118] [Table 1] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3:CNC: Aloterra COOH functionalized CNC
[0136]
[0119] - HCl consumption test using CTAB VES-CNC is important to prove the self-diverting acid property (SDA) for acid well stimulation and formation control. The addition of -CNC (Aloterra, functionalized with -COOH) has a general viscosity increasing effect, especially at higher concentrations, but this effect is almost incremental at low concentrations (Figure 1). - CTAB performed better at higher concentrations (more viscous) in most cases, but was less stable as temperature increased. - Acid consumption tests showed higher viscosity at the peak of consumption (Figure 2). In general, CNC showed an increase in viscosity in the middle of the consumption curve - better diverting. However, CNC showed no effect on the decomposition point - equally good decomposition. - The CNC size (whiskers or nanorods and nanofibers) can still be parameterized to achieve better performance, such as modification of -OH groups of polysaccharides by salification, polymerization or conjugation.
[0137]
[0120] The composition for HCl consumption test was obtained by the same procedure as above, except that CaCl2 was added to the gel solution. The amount of CaCl2 was adjusted based on the amount of HCl consumed.
[0138]
[0121] The self-diverting acid properties of the composition from the HCl consumption test are shown in Figure 2. In Figure 2, the vertical axis shows the viscosity, and the horizontal axis shows the HCl consumption in the composition. The acid consumption test simulated the ability of the composition to react with calcite and dolomite layers. Figures 2(a) and (b) show the viscosity behavior of Example 1 depending on the shear rate at 25°C. Figure 2(c) shows the difference in self-diverting acid properties between Example 1 and Comparative Example 1.
[0139] B) HCl Consumption Test of CTAB VES with Nanoclay The compositions were prepared by mixing the ingredients shown in Table 2. The compositions containing nanoclay were obtained by the same procedure as above, except that nanoclay was used instead of CNC.
[0140]
[0123] [Table 2] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3: Laponite-EP: BYK Nanoclay
[0141]
[0124] - HCl consumption test using CTAB VES-nanoclay is important to prove the self-diverting acid property (SDA) for acid well stimulation and formation control. - The addition of nanoclays generally has the effect of increasing viscosity, especially at higher concentrations, but this effect is mostly incremental. - CTAB performed better at higher concentrations (more viscous) in most cases, but was less stable as temperature increased. - Surface modification with silanes or cationic surfactants can modify the charge and hydrophobicity of nanoclays. - HCl consumption test using nanoclay - The viscosity increased with the addition of 0.25% and 0.5% nanoclay. However, the increase in viscosity from 0.25% to 0.5% was not as clear as that of CNC. This may be due to the aggregation of nanoclay in the acid.
[0142] C) VES surfactant testing using Celluforce sulfated CNC A composition was produced by mixing the components shown in Table 3. A composition containing sulfated CNC was obtained by the same procedure as above, except that sulfated CNC was used instead of CNC.
[0143]
[0126] [Table 3] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3: Sulfated CNC: Celluforce
[0144]
[0127] The self-diverting acid properties of the composition according to the HCl consumption test are shown in Figure 3. In Figure 3, the vertical axis indicates the viscosity, and the horizontal axis indicates the HCl consumption in the composition. Figure 3 shows the viscosity behavior of Examples 4 and 5, and Comparative Example 1.
[0145] Summary of CNC Additive Discussion - The former carboxylated CNC (Aloterra) showed good performance, increasing the maximum viscosity but not affecting the decomposition viscosity. However, the use of sulfated CNC (CelluForce) showed the best viscosity stability at higher temperatures, but the decomposition viscosity also increased. - The addition of sulfated CNC makes CTAB-VES more opaque, but still viscous. - Increasing the concentration of CNC increases the maximum viscosity in the HCl consumption test. - The viscosity at 0% and 18% also increases.
[0146]
[0129] High temperature HCl consumption test As the temperature increased from 25 to 60 °C, the viscosity decreased from about 500 cP to about 200 cP. Compared to the CTAB system without any additive, the VES with 0.5% sulfated CNC showed an increase in viscosity at all temperatures, indicating that the CNC helped the VES maintain a high viscosity at higher temperatures (Figures 3 and 4).
[0147]
[0130] Zwitterionic surfactants and counterion compounds, including sulfated CNC, showed good stability with respect to temperature. With less than 3% total surfactant, the viscosity remained above 100 cP even at 50°C. (Figure 6) Examples of zwitterionic surfactants and counterion compounds are shown in Figure 5.
[0148]
[0131] Compared to all the different VES, CTAB with 0.5% CNC showed the highest viscosity at both 50 and 60 °C. Meanwhile, the zwitterionic / anionic VES showed good viscosity stability from 50 to 60 °C, but exhibited a shift in degradation behavior. All VES systems showed viscosities above 100 cP at 60 °C.
[0149]
[0132] The self-diverting acid properties at high temperatures in the HCl consumption test are shown in Figure 4. In Figure 4, the vertical axis indicates viscosity and the horizontal axis indicates the HCl consumption in the composition. Figures 4(a) and (b) show the viscosity behavior of Example 4 and Comparative Example 1 at high temperatures.
[0150]
[0133] Compositions were prepared by mixing the ingredients shown in Table 4. Compositions containing the following ingredients were obtained by the same procedure as above, except that the following ingredients were used in place of some of the ingredients:
[0151]
[0134] [Table 4] *1:SB3-18:Sigma-Aldrich stearyl sulfobetaine *2: SDBS: Sigma-Aldrich sodium dodecylbenzenesulfonate *3: Sulfated CNC: Celluforce *4: Laponite EP: BYK Nanoclay *5: Laponite RDS: BYK Nanoclay
[0152]
[0135] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 6. Figures 6(a)-(b) show the viscosities of Examples 6-8 and Comparative Example 2 at 25-60°C.
[0153] D) Examination of CTAB VES in acid consumption and addition of small molecules and polymers (FIGS. 7 and 8). A composition was prepared by mixing the ingredients shown in Table 5. The composition was obtained by the same procedure as above, except that the additives were added into the composition.
[0154]
[0137] [Table 5] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3: Sulfated CNC: Celluforce *4 PEG550: Polyethylene glycol with a weight-average molecular weight of 550 *5 PEG2000: Polyethylene glycol with a weight-average molecular weight of 2000
[0155]
[0138] The self-diverting acid properties of the compositions from HCl consumption tests are shown in Figures 7 and 8. Figures 7(a)-(b) show the viscosities of Examples 9-12 and Comparative Example 3 at 25-60°C. Figure 8 shows the additive-based viscosity at 70°C in an 8 wt% HCl consumed solution (up to 20 wt%).
[0156]
[0139] 1. 0.5% CNC showed good improvement in viscosity compared with no additive and could also increase the performance at 60°C, which is consistent with our previous results. 2. The addition of 0.5% ethylene glycol may not significantly affect the viscosity at high temperatures. 3. The addition of 0.5% polyethylene glycol (PEG) slightly increases the viscosity at both room temperature and 60°C. 4. The effect of PEG depends on its molecular weight, with the higher the molecular weight the greater the stability.
[0157] At 70°C, the evaporation of CTAB is intense. By controlling the same working time, the viscosity can be compared relatively. The results showed that CNC increases the viscosity of CTAB VES, and the addition of higher MW PEG to CTAB VES and CNC also improves the viscosity.
[0158] E) Testing of silane-functionalized CNCs: Procedure and synthesis of silane-functionalized CNCs with various silane structures (Figure 9): Silane modification by direct mixing of silane agent and sulfated CNC powder: 1. To a vial containing 500 mg of sulfated CNC powder, 2 mL of silane was added. 2. Vigorous stirring was used to ensure uniform dispersion of the powder. 3. The reaction was heated to 40° C. and the mixture was allowed to react for 36 hours. 4. The suspension was purified by vacuum filtration and washed with 50 mL of ethanol.
[0159]
[0142] For APTMS: - After functionalization, both the initial pyrolysis temperature and the temperature of maximum decomposition rate increase, which can be attributed to the interaction between silane and CNC (Si-OC). The increase in residual mass is due to siloxyl groups, which is supported by the literature.
[0160]
[0143] For AEAPTMS: - Both the initial pyrolysis temperature and the temperature of maximum decomposition rate increase. - There is no difference in the residual mass, which can be attributed to lower functionalization (smaller NH peak).
[0161] Summary of silane surface functionalized CNCs and viscosity measurement results: The formulation 3%CTAB+0.5%NaSal+0.5%(CNC) after 12% HCl consumption (maximum 20%) was tested. According to the viscosity test results, all silane modified CNCs showed negligible viscosity change with respect to unmodified CNCs, which can be attributed to the fact that all silane agents make CNCs more hydrophobic (Figure 10). Thus, silane modified CNCs tend to form large aggregates and do not disperse well in VES. 1. Four silane-modified CNCs were prepared. However, FTIR and GC-MS suggest that the functionalization is not successful. TGA of CNC-APTES and CNC-AEAPTMS showed significant differences from unmodified CNCs, while CNC-GPTES showed no difference. When prepared with CTAB and NaSal, CNC-GPTES showed no effect on viscosity, while CNC-APTES and CNC-AEAPTMS showed a negative effect on viscosity. Tests at higher temperatures will be conducted to optimize the functionalization. 2. Graphene oxide was added as a second additive to the zwitterionic / anionic system, but the effect of GO on viscosity is not significant. 3. The viscosity results in zwitterionic VES also showed the same results, all silane modified CNCs showed lower viscosity than unmodified CNCs, which may be attributed to the silane agents making all CNCs more hydrophobic.
[0162] Procedure for cationic modification of CNC: Preparation of cationic CNCs 1. Sulfated CNC aqueous suspension (2 wt%) was treated with dilute alkaline solution (NaOH, 2 wt%) for 30 min at room temperature. 2. 2,3-Epoxypropyltrimethylammonium chloride (EPTMAC) was added dropwise as a catalyst to the suspension containing NaOH, and the reaction was continued at 65°C for 6 hours. 3. After the reaction, the suspension (about 2 wt%) was precipitated in ethanol and the product was collected by centrifugation. 4. EPTMAC-cationic cellulose nanocrystals (cationic-CNCs) were dialyzed in distilled water for 5 days and redispersed (approximately 2 wt%).
[0163]
[0146] IR and DSC data confirmed the successful grafting of cationic silanes onto CNCs (Figure 11).
[0164] F) Testing of polymer-grafted CNCs Preparation of polymer-grafted CNCs Step 1: Synthesis of CNC-initiator 1. Sulfated CNCs (1 g) were dispersed in anhydrous N,N-dimethylformamide (DMF) (60 mL) by stirring and sonicating for 1 h at room temperature. Triethylamine (TEA) (2.50 g) and N,N-dimethyl-4-aminopyridine (DMAP) (180 mg) were added to the suspension, after which a solution of 2-bromoisobutyryl bromide (BiBB) (7.80 g) in DMF was added dropwise to the mixture for 2 h. 2. The mixture was stirred for another 12 hours at room temperature, and then 10 mL of methanol was introduced. After centrifugation (4.4k rpm), the crude product was washed three times with methanol.
[0165] Step 2: Synthesis of polymer-grafted CNC 1. A mixture of CNC-Br suspension (30 mg), monomers (poly(ethylene glycol) methyl ether methacrylate (PEGMEMA), 2-(dimethylamino)ethyl methacrylate (DMAEMA), 2 g), methanol (~2.0 mL) and Cu(I)Br (28 mg) was placed in a Schlenk tube with a magnetic stir bar. 2. After purging with N2 for 30 min, degassed 1,1,4,7,10,10-hexamethyltriethylenetetramine (HMTETA) (20 μL in 1 mL of methanol) was injected into the mixture. 3. The polymerization was carried out overnight at room temperature and then the reaction was quenched by opening the Schlenk tube to air. 4. After dilution with ethanol, the suspension was centrifuged (4.4k rpm) and the supernatant was collected and washed three times with methanol.
[0166]
[0149] A composition was produced by mixing the components shown in Table 6. The composition was obtained by the same procedure as above, except that grafted CNC was used.
[0167]
[0150] [Table 6] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3:Sulfation-CNC:Celluforce *4 Cationic-CNC: Modified-CNC obtained by the above method *5 PDMAEMA-CNC: Grafted CNC obtained above *6 CNC-PVA-premix: A mixture of sulfated CNC (0.5 wt%) and polyvinyl alcohol (0.5 wt%)
[0168]
[0151] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 14. Figure 14 shows the viscosity of Examples 13-16 in a 12 wt% HCl consumption solution (up to 20 wt%) at 25-60°C.
[0169]
[0152] Synthesis and surface initiated polymerization (SIP) results on CNCs FTIR spectra showed successful functionalization of the ATRP-initiator and polymerization of PDMAEMA by detecting C=O stretching (Figure 12). With ATRP-initiator alone, CNCs have lower thermal stability (161°C). After SIP polymerization, the denaturation temperature increases to 231°C. In addition, CNC-PDMAEMA has a lower residual mass, which also confirmed the successful polymerization or grafting of PDMAEMA on CNCs. Similarly, successful grafting of CNC-PPEGMEMA was shown in Figure 13.
[0170]
[0153] Viscosity measurement results The synthesis of cationic-CNC and polymer-grafted-CNC was performed. The results showed successful functionalization, which was evidenced by FTIR and TGA (Figures 12-13). Cationic-CNC and polymer-grafted-CNC showed the best improvement in viscosity at both room temperature and 60 °C. CNC-polyvinyl alcohol or CNC-PVA premix solid (1:1) was also tested as an additive. 1 wt% was added to VES. This showed the same improved viscosity as when 0.5% of each was added directly to VES. The results are summarized in Figure 14.
[0171] G) Testing of Additive Polymers G-1. Example A Compositions were made by mixing the ingredients shown in Table 6 according to the following method.
[0172] Typical Preparation Procedure for 12% HCl Spent Solution (20% Maximum, 8% Residual) 1. A master solution of 2 wt% CNC was prepared by dissolving CNC in water and sonicating for 1 h. 2. 2.5 g of 2 wt% CNC solution was added to a 20 mL vial. 3. 50mg to 300mg of polymer was added to a vial. 4. 2.3 g of hydrochloric acid was added to the vial. 5. 4.2 g of water was added to the vial. 6. The solution was vertex mixed and sonicated until the polymer was completely dissolved. 7. 0.3 g of CTAB was added to the solution and vertex mixed until the CTAB was completely dissolved. 8. A master solution of 5 wt% NaSal was prepared by dissolving NaSal in water. 9. 1 g of 5 wt% NaSal solution was added to the CTAB solution and vertex mixed. A gel-like solution formed within a few seconds. 10. 1.8 g of CaCl2 was added to the gel solution and vertex mixed. From the HCl consumed, 1 g of HCl was calculated for every 1.5 g of CaCl2. 11. The solution was allowed to stand overnight to remove bubbles.
[0173]
[0156] [Table 7] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3: Sulfated CNC: Celluforce *4 PSS: Sigma-Aldrich poly(4-styrenesulfonic acid-co-maleic acid) sodium salt *5 PAM: Sigma-Aldrich polyacrylamide *6 PVP: Sigma-Aldrich polyvinylpyrrolidone *7 PAH: Sigma-Aldrich poly(allylamine hydrochloride) *8 PDADMAC: Sigma-Aldrich poly(diallyldimethylammonium chloride)
[0174]
[0157] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 16. Figure 16 shows the difference in additives in a 12% HCl consumption solution (20% max, 8% residual) and viscosity based on additive content.
[0175]
[0158] PVP: With the addition of 0.5% PVP, the results showed an increase in viscosity. With the addition of 1% PVP, the results showed a larger increase in viscosity, but not significantly different from the 3% addition attempted at 70°C, as shown later.
[0176]
[0159] PAM: The addition of 0.5% PAM did not show any difference in viscosity at 60°C, but with the addition of 1% or 3%, the solution became too viscous and -1 (Limit of viscometer)
[0177] PAHs, PDADMAC and PSS The addition of PAH and PDADMAC does not affect the viscosity, but PSS reduces the viscosity.
[0178]
[0161] The acid consumption test also showed consistent behavior with PVP. The HCl consumption test involves preparing different HCl and CaCl2 concentrations to simulate HCl consumption conditions. The 0.5% CNC VES solution showed self-diverting properties under the full 20% HCl consumption test and full 28% HCl test conditions. The addition of 0.5% PVP showed the same self-diverting properties, but with a higher viscosity.
[0179]
[0162] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 17. Figure 17 shows the viscosity based on PVP.
[0180]
[0163] 0.5% CNC VES solution exhibits self-diverting properties under the conditions of 20% total HCl consumption test and 28% total HCl test. The addition of 0.5% PVP exhibits the same self-diverting properties but with a higher viscosity.
[0181]
[0164] Based on the viscosity at higher temperatures, further testing was performed on these polymers (Figures 18-20).
[0182] G-2. Example B The compositions were prepared by mixing the ingredients shown in Tables 8 and 9. The compositions were obtained by the same procedure as above.
[0183]
[0166] [Table 8]
[0184]
[0167] [Table 9]
[0185]
[0168] *1: CTAB: Cetyltrimethylammonium bromide *2:NaSal: Sodium salicylate *3: Sulfated CNC: Celluforce *4: PVP (Mw=10000): Sigma-Aldrich polyvinylpyrrolidone (Mw=10000) *5: PVP (Mw=40000): Sigma-Aldrich polyvinylpyrrolidone (Mw=40000) *6: P4VP: Sigma-Aldrich poly(4-vinylpyridine) (Mw=60000) *7: PAG A (Mw 84000): Sigma-Aldrich Poly(ethylene glycol)-co-poly(propylene glycol)-co-poly(ethylene glycol) with Mw 84000 *8: PAG B (Mw44000): Sigma-Aldrich Poly(ethylene glycol)-co-poly(propylene glycol)-co-poly(ethylene glycol) with Mw44000 *9: PAG C (Mw 11000): Sigma-Aldrich Poly(ethylene glycol)-co-poly(propylene glycol)-co-poly(ethylene glycol) with Mw 11000 *10:PEI: Sigma-AldrichPolyethyleneimine with Mw10000 *11: PA: Sigma-Aldrich polyaniline with Mw65000
[0186]
[0169] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 18. Figure 18(a) shows the viscosity of a composition containing PVP with Mw 10000. Figure 18(b) shows the viscosity of a composition containing PVP with Mw 40000. Figure 18(c) shows the viscosity of a composition containing P4VP.
[0187]
[0170] PVP (Mw 10000) did not show a significant difference in viscosity, but PVP (Mw 40000) showed an increase in viscosity. This suggested that the molecular weight of PVP affects the viscosity of the VES solution. An increase can be detected when comparing the polymer only solution and the solution without additive. P4VP does not show a significant difference in viscosity. The 1% addition showed a slight increase, but the difference is very slight.
[0188]
[0171] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 19. Figure 19(a) shows the viscosity of the composition containing PAG A (Mw 84000). Figure 19(b) shows the viscosity of the composition containing PAG B (Mw 44000). Figure 19(c) shows the viscosity of the composition containing PAG C (Mw 11000).
[0189]
[0172] Poly(ethylene glycol)-co-poly(propylene glycol)-co-poly(ethylene glycol) triblock copolymers show a negative impact on viscosity. By adding 0.5% of the polymer, the viscosity drops to less than 200 cP. There is no significant difference in viscosity between 8.4k, 4.4k and 1.1k, suggesting that this result may be due to the amphiphilic blocks of the polymer, which affect the micellar condition.
[0190]
[0173] The self-diverting acid properties of the compositions from the HCl consumption test are shown in Figure 20. Figure 20(a) shows the viscosity of the composition containing PAG A (Mw 84000). Figure 20(b) shows the viscosity of the composition containing PAG B (Mw 44000).
[0191] Polyethyleneimine (PEI, Mw 10000, branched) showed a positive effect on viscosity at 0.5% and could decrease viscosity above 0.5%. However, the effect on viscosity was not very effective. Polyaniline (PA, Mw 65000, emeraldine base) showed a large increase at 1%, but no significant difference at 0.5wt% and 3%. This may be due to the acidic condition causing emeraldine base to transition to a quaternary salt and interacting with CNC.
[0192] In summary, eight different polymers at three different concentrations were tested as co-additives. The results showed that PVP(40K) showed a clear increase in viscosity at 0.5% and 1%, which is consistent with previous results. PVP(10K) and P4VP(65K) did not show significant differences in viscosity. PEI(10K, branched) showed a slight increase in viscosity. However, triblock copolymer of poly(ethylene glycol)-co-poly(propylene glycol)-co-poly(ethylene glycol) reduced the viscosity of the VES solution.
[0193]
[0176] Other embodiments of the present invention are as follows.
[0194] 1. Viscoelastic surfactants, and Modified Nanomaterials A composition for forming an oil well or a gas well, comprising:
[0195] 2. The composition of claim 1, wherein the nanomaterial comprises nanocellulose.
[0196] 3. The composition of claim 1 or 2, wherein the nanomaterial comprises at least sulfate groups, sulfite groups, carboxy groups, ethylene oxide chains, amino groups, ester groups, silane groups or tertiary ammonium groups on its surface.
[0197] 4. The composition of claim 3, wherein the nanoparticles contain sulfate groups on their surface.
[0198] 5. A composition according to any one of claims 1 to 4, wherein the modified nanomaterial has a grafted polymer on its surface.
[0199] 6. A composition according to any one of claims 1 to 5, wherein the viscoelastic surfactant comprises a surfactant and a counterion.
[0200] 7. The composition of claim 6, wherein the counterion comprises an organic acid salt.
[0201] 8. The composition of claim 6 or 7, wherein the counterion comprises at least a carboxylate or a sulfonate.
[0202] 9. The composition according to any one of claims 6 to 8, wherein the surfactant comprises at least one selected from the group consisting of cationic surfactants, anionic surfactants, zwitterionic surfactants and amphoteric surfactants.
[0203] 10. A surfactant having the formula (1): R 1 -N(R 2 )3 + X - (1) (In the formula, R 1is an aliphatic group having 10 to 20 carbon atoms, R 2 is an aliphatic group having 1 to 6 carbon atoms, and X - The composition of any one of claims 6 to 9, comprising a compound of the formula:
[0204] 11. Particles other than nanoparticles, Polymers, and Molecules that lead to nanostructured composites 11. The composition of claim 1, further comprising at least one additive selected from the group consisting of:
[0205] 12. The composition of claim 11, wherein the polymer comprises at least polyacrylamide, poly(allylamine hydrochloride), poly(ethylene glycol), polyethyleneimine, or polyvinyl alcohol.
[0206] 13. A method of producing a composition, comprising: adding the modified nanomaterial; and Adding a viscoelastic surfactant The method includes:
[0207] 14. A method of forming an oil or gas well, comprising: solvent, Viscoelastic surfactants, modified nanomaterials, and Acid Material preparing a fluid comprising: Introducing fluid into the well The method includes:
[0208]
[0177] Patents: 1. Whalen R T. Viscoelastic surfactant fracturing fluids and a method for fracturing subterranean formations: US Patent 6,035,936[P]. 2000-3-14. 2. Hughes T L, Jones T G J, Tustin G J. Viscoelastic surfactant based gelling composition for wellbore service fluids: U.S. Patent 6,232,274[P]. 2001-5-15. 3. Dahayanake M S, Yang J, Niu J H Y, et al. Viscoelastic surfactant fluids and related methods of use: U.S. Patent 6,258,859[P]. 2001-7-10. 4. Nelson E B, Lungwitz B, Dismuke K, et al. Viscosity reduction of viscoelastic surfactant based fluids: U.S. Patent 6,881,709[P]. 2005-4-19. 5. Crews J B, Huang T. Use of nano-sized phyllosilicate minerals in viscoelastic surfactant fluids: U.S. Patent 9,145,510[P]. 2015-9-29. 6. Pandya N K, Wadekar S D, Pathre G S. Branched viscoelastic surfactant for high-temperature acidizing: U.S. Patent 9,359,545[P]. 2016-6-7 7. Li L, Lin L, Abad C, et al. Acidic internal breaker for viscoelastic surfactant fluids in brine: U.S. Patent 9,284,482[P]. 2016-3-15. 8. Huang T. Mutual solvent-soluble and / or alcohol blends-soluble particles for viscoelastic surfactant fluids: U.S. Patent 8,653,012[P]. 2014-2-18. 9. Svoboda C, Moore L T, Evans F E. Viscoelastic surfactant based wellbore fluids and methods of use: U.S. Patent 9,353,306[P]. 2016-5-31. 10. Gurmen M N, Fredd C N. Viscoelastic surfactant rheology modification: U.S. Patent 9,034,806[P]. 2015-5-19.
[0209]
[0178] Publications: 1. Yang J. Viscoelastic wormlike micelles and their applications. Current opinion in colloid & interface science. 2002 Nov 30;7(5):276-81. 2. Olsson U, Soederman O, Guering P. Characterization of micellar aggregates in viscoelastic surfactant solutions. A nuclear magnetic resonance and light scattering study. The Journal of Physical Chemistry. 1986 Oct;90(21):5223-32. 3. Fischer P, Rehage H. Rheological master curves of viscoelastic surfactant solutions by varying the solvent viscosity and temperature. Langmuir. 1997 Dec 24;13(26):7012-20. 4. Samuel M, Polson D, Graham D, Kordziel W, Waite T, Waters G, Vinod PS, Fu D, Downey R. Viscoelastic surfactant fracturing fluids: applications in low permeability reservoirs. InSPE Rocky Mountain Regional / Low-Permeability Reservoirs Symposium and Exhibition 2000 Jan 1. Society of Petroleum Engineers. 5. Lungwitz BR, Fredd CN, Brady ME, Miller MJ, Ali SA, Hughes KN. Diversion and cleanup studies of viscoelastic surfactant-based self-diverting acid. SPE Production & Operations. 2007 Feb 1;22(01):121-7. 6. Huang T, Crews JB. Nanotechnology applications in viscoelastic surfactant stimulation fluids. SPE Production & Operations. 2008 Nov 1;23(04):512-7. 7. Hoffmann H, Thunig C, Schmiedel P, Munkert U, Ulbricht W. The rheological behaviour of different viscoelastic surfactant solutions: systems with and without a yield stress value. Tenside, surfactants, detergents. 1994;31(6):389-400. 8. Fischer P, Rehage H. Non-linear flow properties of viscoelastic surfactant solutions. Rheologica acta. 1997 Jan 1;36(1):13-27. 9. Cooper-White JJ, Crooks RC, Boger DV. A drop impact study of worm-like viscoelastic surfactant solutions. Colloids and Surfaces A: Physicochemical and Engineering Aspects. 2002 Oct 16;210(1):105-23. 10. Hull K L, Sayed M, Al-Muntasheri G A. Recent Advances in Viscoelastic Surfactants for Improved Production From Hydrocarbon Reservoirs[J]. SPE Journal, 2016. 11. Yang J, Lu Y, Zhou C, et al. Supramolecular Viscoelastic Surfactant Fluid for Hydraulic Fracturing[C] / / SPE North Africa Technical Conference and Exhibition. Society of Petroleum Engineers, 2015.
Claims
1. viscoelastic surfactants, and including modified nanomaterials, A composition for oil or gas well formation.
2. 10. The composition of claim 1, wherein the modified nanomaterial comprises nanocellulose.
3. 3. The composition of claim 1 or 2, wherein the modified nanomaterial has on its surface at least one selected from the group consisting of sulfate groups, sulfite groups, carboxy groups, ethylene oxide chains, amino groups, ester groups, silane groups and tertiary ammonium groups.
4. The composition of claim 3 , wherein the modified nanomaterial has sulfate groups on its surface.
5. The composition of claim 1 , wherein the modified nanomaterial has a grafted polymer on its surface.
6. The composition of claim 1 , further comprising a counterionic compound having a counterion moiety for the ionic group of the viscoelastic surfactant.
7. The composition of claim 6 , wherein the counterionic compound comprises an organic acid salt.
8. The composition of claim 6 or 7, wherein the counterionic compound comprises at least a carboxylate or a sulfonate.
9. 9. The composition of claim 6, wherein the viscoelastic surfactant comprises at least one selected from the group consisting of cationic surfactants, anionic surfactants, zwitterionic surfactants and amphoteric surfactants.
10. The viscoelastic surfactant has the formula (1): R 1 -N(R 2 ) 3 + X - (1) (In the formula, R 1 is an aliphatic group having 10 to 20 carbon atoms, R 2 is an aliphatic group having 1 to 6 carbon atoms, X - The composition according to claim 6 , comprising a compound represented by the formula:
11. The composition according to claim 1 , further comprising a polymer and / or an additive.
12. 12. The composition of claim 11, wherein the polymer comprises at least one selected from the group consisting of polyacrylamide, poly(allylamine hydrochloride), poly(ethylene glycol), polyethyleneimine polyvinyl alcohol, poly(4-styrenesulfonic acid-co-maleic acid), polyvinylpyrrolidone, polyallylamine, and poly(diallyldimethylammonium), polyaniline, poly(4-vinylpyridine), polyaniline emeraldine.
13. The composition of claim 1 further comprising a solvent.
14. 1. A method of making a composition, comprising: The method includes the step of combining a modified nanomaterial and a viscoelastic surfactant.
15. 1. A method for forming an oil or gas well, comprising: The method includes preparing a fluid including a solvent, a viscoelastic surfactant, a modified nanomaterial, and an acid material, and introducing the fluid into a well.
Citation Information
Cited By
Method for predicting acid etched surface morphology
JP2026054542A
Method for predicting acid-etched surface morphology
JP7845710B2